Jim Kennedy operating press machine at Hercules Port Ewen plant - Hercules Incorporated (1945)
General view of employee Jim Kennedy operating a press machine used to fill electric blasting caps with an explosive charge at the Hercules Powder Company plant in Port Ewen, New York. The operation was remote-controlled and, per notations accompanying the photograph, the machine typically operated behind a concrete barricade, which is open here for the purposes of the photograph. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) specialized in the manufacture of explosives and smokeless powders. During World War II, the company's Port Ewen plant produced a range of special detonators designed for military use.
Keywords: Explosives, Military; Detonators; Employees; Chemical industry; Propellants; Hercules Incorporated; World War (1939-1945); Military supplies; Corporations; Explosives; Defense industries; Machinery; Kennedy, Jim